(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Leishmaniasis is a the third most prevalent vector borne disease. The current study showed the prevalence of this disease according togender, age, body parts and number of lesions. This study also reveals the major cause and symptoms of leishmaniasis inMuzaffargarh, Punjab. This was the first study to observe the leishmaniasis patients in the district Muzaffargarh of Punjab, Pakistan;also, might helpful in studying disease in other parts of Pakistan. Parasitic disease, leishmaniasis is caused by an obligate intercellularparasite belonging to genus Leishmania. The study was conducted from January to August 2021 to determine the prevalence ofleishmaniasis in Muzaffargarh, Punjab. A total 141 reports were studied. Infected people with cutaneous leishmaniasis were 41(87%). Highest prevalence was observed in July (n=10, 24%). The highest affected age was more than 16 years, of 21 (45%)individuals. There were 18 (44%) individuals having cutaneous lesions on their hands, arms, ear, legs and feet, while 23 (56%)individuals were having cutaneous lesions on their face. Male to female ratio was 3:4, respectively. Patients were treated withintralesional injections of sodium stibogluconate. Analysis revealed that it is more prevalent in female as compared to male;moreover, adults were more frequently affected than children.